Numerical and Experimental Investigations of Steady Micro-Tip Injection on a Subsonic Axial-Flow Compressor Rotor - Xingen Lu; Wuli Chu; Junqiang Zhu; Zhiting Tong (International Journal of Rotating Machinery)
Steady tip injection has been demonstrated to be an effective means of extending the stable operating range of a tip-critical compressor. This study presents a state-of-the-art design for the tip injection through the casing with flush-mounted inclined holes and the effectiveness of steady micro-air injection to enhance stability in a subsonic axial-flow compressor rotor using an external-air supply. For the tested rotor, experimental results demonstrate that at 53% design speed, the stalling mass flow can be reduced by 7.69% using an injected mass flow equivalent to 0.064% of the annulus flow. Time-dependent CFD simulations were conducted to identify the physical mechanic that accounts for the beneficial effects of the steady micro-air injection on the performance and stability of the compressor. Detailed analyses of the flow visualization at the tip have exposed the different tip flow topologies between the cases without tip injection and with tip injection. It was found that the primary stall margin enhancement afforded by the steady micro-air injection is a result of the tip-clearance flow manipulation. The repositioning of the tip-clearance vortex further towards the trailing edge of the blade passage and delaying the movement of incoming/tip-clearance flow interface to the leading edge plane are the physical mechanisms responsible for extending the compressor stall margin.